Innovative Pedagogical Strategies as Predictors of Entrepreneurial Motivation in Secondary Education - Edwin Edwin; Made Hery Santosa; I Wayan Widiana; Tin T. Dang (Yayasan Keluarga Guru Mandiri, 2026)
This study explores the impact of innovative pedagogical strategies on enhancing entrepreneurial motivation among high school students in Denpasar, Indonesia. Recognizing the role of entrepreneurship education in fostering creative, independent, and adaptive learners, this research focuses on two innovative approaches: Project-Based Learning and Problem-Based Learning. Using a quantitative, ex post facto design, data were collected from 99 students who had completed entrepreneurship courses using a validated Likert-scale questionnaire. Analysis using simple linear regression revealed that pedagogical strategies accounted for 20.2 per cent of the variance in entrepreneurial motivation, including intrinsic factors such as passion and autonomy, as well as extrinsic factors such as social recognition and financial independence. The study demonstrates that participatory, context-based learning significantly boosts students' entrepreneurial drive and engagement. The findings contribute to educational science by highlighting how innovative teaching methods not only enhance academic performance but also cultivate entrepreneurial mindsets among high school students, offering practical recommendations for curriculum development and policy-making in entrepreneurship education.